2005
DOI: 10.1002/ca.20086
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of multiple anomalies in the carpal tunnel

Abstract: We determined the frequency of anomalous structures within the carpal tunnels of 89 cadaveric forearm-hand specimens. We also examined these same specimens for variations in the branching pattern of the median nerve, and analyzed the range in length and width of the lumbricals. Many of the hands contained extra tendinous slips from the long flexors within the tunnel, subligamentous thenar branches of the median nerve, or lumbricals with bipennate origins. Only one hand had an anomalous muscle belly within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…Because of the perforation of both the MN and AIN and the coursing of the AIN deep to the tendon of GM, this donor may have suffered from symptoms related to PS and AINS (Gainor and Jeffrid, 1987;Proudman and Menz, 1992;Eid and Otsuki, 2009). There is also the possibility that this donor had suffered from chronic CTS, because the PMA, with a diameter of 2.1 mm, was superficial to the MN inside the CT (Barfred et al, 1985;Gassner et al, 2002;Barbe et al, 2005). In fact, the actual diameter of the PMA before death may have been larger.…”
Section: Discussionmentioning
confidence: 93%
“…Because of the perforation of both the MN and AIN and the coursing of the AIN deep to the tendon of GM, this donor may have suffered from symptoms related to PS and AINS (Gainor and Jeffrid, 1987;Proudman and Menz, 1992;Eid and Otsuki, 2009). There is also the possibility that this donor had suffered from chronic CTS, because the PMA, with a diameter of 2.1 mm, was superficial to the MN inside the CT (Barfred et al, 1985;Gassner et al, 2002;Barbe et al, 2005). In fact, the actual diameter of the PMA before death may have been larger.…”
Section: Discussionmentioning
confidence: 93%
“…As discussed, the presence of additional tendon slips are frequently reported, particularly for the FDP, FDS, and FPL (Linburg and Comstock, 1979;Steinberg and Szabo, 1996;Leijnse et al, 1997;Lindley and Kleinert, 2003;Barbe et al, 2005), with the incidence of such anomalies ranging from 5 to 25%. While the incidence of additional tendon / muscle slips were not assessed in our cadaveric study, the incidence of accessory muscle bellies or heads was found to be substantially lower at 0.16% of forearms or 0.32% of individuals, mirroring the rare reporting of true accessory muscles in reported studies.…”
Section: Discussionmentioning
confidence: 95%
“…While the incidence of additional tendon / muscle slips were not assessed in our cadaveric study, the incidence of accessory muscle bellies or heads was found to be substantially lower at 0.16% of forearms or 0.32% of individuals, mirroring the rare reporting of true accessory muscles in reported studies. These studies comprise accessory muscles of the FDS, FDP, and FPL (Still and Kleinert, 1973;Lahey and Aulicino, 1986;Schon et al, 1992;Steinberg and Szabo, 1996;Wahba et al, 1998;Elliot et al, 1999;Koizumi et al, 2002;Kobayashi et al, 2003;Lindley and Kleinert, 2003;Barbe et al, 2005). In these studies, the variations in muscle location, attachments and structure have been variably associated with variations in local vasculature and innervation, and furthermore have been associated with clinical sequelae including compression neuropathies and iatrogenic injury.…”
Section: Discussionmentioning
confidence: 95%
“…Investigators have developed in vivo primate models (Blake et al 2002;Byl et al 1996cByl et al , 1997 and in vivo rat models (Barbe et al , 2005Barbe 2002, 2004;Clark et al 2004) to study the etiology of FHd. The hypothesis for the primate studies was that high levels of repetitive, near simultaneous movements would lead to central somatosensory changes in the topography of the hand that would ultimately interfere with normal movement control.…”
Section: The Benefits Of Animal Versus Clinical Models For Studying Hmentioning
confidence: 99%